In Vitro Antiproliferative Activity of Extracts of Carlina acaulis subsp. caulescens and Carlina acanthifolia subsp. utzka - Strzemski, Maciej; Wojnicki, Kamil; Sowa, Ireneusz; Wojas-Krawczyk, Kamila; Krawczyk, Paweł; Kocjan, Ryszard; Such, Justyna; Latalski, Michał; Wnorowski, Artur; Wójciak-Kosior, Magdalena (Frontiers in Pharmacology, 2017)
Various species of the Carlina genus have been used in traditional medicine in many countries to treat numerous skin disorders, including cancer. The objective of this work was to assess the anticancer properties of root and leaf extracts from C. acaulis subsp. caulescens and C. acanthifolia subsp. utzka. Anti-tumor properties of the extracts were explored using a tetrazolium-based cell viability assay and flow cytometric apoptosis analysis, followed by immunodetection of phosphoactive ERK1/2 in UACC-903, C32 and UACC-647 human melanoma cell lines. Normal human fibroblasts were used as a control. Leaf extracts inhibited the viability of all tested melanoma cell lines in a dose-dependent fashion while the fibroblasts were less sensitive to such extract. The root extracts inhibited the proliferation of UACC-903 and UACC-647 cells only at the highest doses (300 μg/mL). However, the C32 and fibroblast cells exhibited an increase in the cellular proliferation rate and no caspase activity was observed in response to the root extracts (100 μg/mL). An increase in caspase activity was observed in melanoma cells treated with the leaf extracts of both Carlina species. Leaf extracts from C. acaulis subsp. caulescens (100 μg/mL) inhibited proliferatory ERK1/2 in UACC-903 and C32 cells, as demonstrated by the decrease in ERK1/2 phosphorylation. No reduction in phospho-ERK1/2 was observed in the tested cell lines treated with the root extracts, apart from UACC-647 after incubation with the C. acanthifolia subsp. utzka root extract (100 μg/mL). There was no change in ERK1/2 phosphorylation in the fibroblasts. The extracts from the leaves and roots were analyzed by HPLC and the analysis showed the presence of triterpenes and phenolic acids as the main extract components. The research demonstrated that the extracts from the leaves of the plants were cytotoxic against the human melanoma line and induced apoptosis of the cells. The triterpene fraction present in the tested extracts may be responsible for this activity.